EFFECTS OF DIETARY ADENINE ON GROWTH, LIPID SECRETION, AND LIVER LIPID CONTENT - Yohanes Buang (Universitas Gadjah Mada, 2010)
The effects of dietary adenine on growth, lipid secretion, and liver lipid contents were studied. Rats were paired-fed 0.25 % adenine diet or a diet without adenine for 10 days. The final body weight and relative liver weight were recorded. Serum lipid profiles were measured using enzyme assay kits. Lipids of liver tissues were extracted and the lipid contents were determined. A peach of liver was prepared to determine the activities of fatty acid synthase (FAS) and fatty acid β-oxidation. The results showed that animals fed an adenine diet reduced slightly body weight and relative liver weight and promoted serum triglyceride (TG), phospholipids (PL), total cholesterol, and high density lipoprotein concentrations. Their promotions were approximately by 74%, 20%, 27%, and 27%, respectively. The liver PL content increased significantly whereas the promotions of liver TG and cholesterol failed to reach significant level. Furthermore, the FAS activity slightly stimulated, but fatty acid β-oxidation significantly decreased. In conclusion: dietary adenine suppressed slightly growth of body weight and relative liver weight but promoted secretion of lipid compounds from liver tissue into extra-hepatic and liver PL content. The enzyme activity of lipogenic was slightly stimulated whereas the lipolytic was significantly inhibited.